Accounts, Accounting and Accountability: Essays in Memory of Peter Bird. - Frishkoff, Paul; Moriarty, Shane R. (The Accounting Review, 1990)
Abstract Reviews the book `Accounts, Accounting and Accountability: Essays in Memory of Peter Bird,' by G. MacDonald and B.A. Rutherford.